Accelerating investment in developing economies - Agarwala, A. N.; Singh, Sampat Pal (London : Oxford University Press, 1969)
This book examines investment problems and their policies and also it discusses the problems of industrial growth. It provides solutions to some of the existing investment problems in developing countries.
Includes bibliographical references.
ucj 15/01/2019
Loans
Keywords: Finance